Pola Asuh Ibu Tiri dalam Membangun Karakter Anak Pra Sekolah - Siti Nurhaliza; Yusmami (Syifaul Qulub: Jurnal Bimbingan dan Konseling Islam, 2021)
This study discusses the Stepmother Parenting in Building the Character of Pre-School Children in Alur Nunang Village, Kec. Banda Mulia is experiencing various obstacles. This study aims to determine the parenting style of stepmothers in building the character of pre-school children in the village of groove nunang, sub-district. Banda Mulia and to find out the stepmother's obstacles in building the character of pre-school children in the village of groove nunang kec. Noble band. The type of approach used in this research is qualitative research. The results showed that stepmother parenting in building character in pre-school children in Alur Nunang village, Kec. Banda Mulia is to educate them gently, we position them as our biological children so that their mental and character can be confident and as if they still have a biological mother. Parenting should not be authoritarian, because it will result in their mental and self-confidence will be down. The influence of the stepmother's parenting style on the child's character is very important, namely in the form of preventive action (prevention). Then in the form of repressive actions (active), as well as curative actions (supervision) on children's behavior both at home and outside the home. factors and barriers to stepmothers in building the character of pre-school children in Alur Nunang Village, Kec. Banda Mulia are children who have a stepmother who are often feared by their friends playing in their environment, saying that the stepmother is very cruel, so that the psychology of the children becomes timid in front of their stepmother, then automatically, the stepmother's upbringing in building the children's character will experience obstacles